2004
DOI: 10.1242/jcs.00968
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic recruitment of the adaptor protein LAT: LAT exists in two distinct intracellular pools and controls its own recruitment

Abstract: The integral membrane adaptor protein linker for activation of T cells (LAT) couples the T-cell receptor (TCR) with downstream signalling and is essential for T-cell development and activation. Here, we investigate the dynamic distribution of LAT-GFP fusion proteins by time-lapse video imaging of live T lymphocytes interacting with antigen-presenting cells. We show that LAT forms two distinct cellular pools, one at the plasma membrane and one that co-distributes with transferrin-labelled intracellular compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
121
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 21 publications
16
121
0
Order By: Relevance
“…For example, initial recruitment of the membrane adaptor protein LAT (linker for activation of T cells) is mediated by cholesterol-sphingolipid raft domains at the IS. 33 Although we did not study this question further, it is intriguing that SNX27 was also identified as a protein with a putative CRAC (cholesterol recognition amino acid consensus) motif on its PDZ domain, 34 as these motifs can also mediate membrane localization.…”
Section: Phosphoinositide Dynamicsmentioning
confidence: 96%
“…For example, initial recruitment of the membrane adaptor protein LAT (linker for activation of T cells) is mediated by cholesterol-sphingolipid raft domains at the IS. 33 Although we did not study this question further, it is intriguing that SNX27 was also identified as a protein with a putative CRAC (cholesterol recognition amino acid consensus) motif on its PDZ domain, 34 as these motifs can also mediate membrane localization.…”
Section: Phosphoinositide Dynamicsmentioning
confidence: 96%
“…2 This process ensures a steady supply of TCRs at the IS to sustain signaling for T-cell activation 3 and has been co-opted by other receptors, such as the transferrin receptor (TfR) and the chemokine receptor CXCR4, 4,5 as well as membrane-bound signaling mediators, such as the kinase Lck and the adaptor LAT. 6,7 Receptor recycling is orchestrated by the small GTPases Rab4 and Rab11. 8 Cargo specificity is achieved with the assistance of specific regulators and effectors.…”
mentioning
confidence: 99%
“…4 Central membrane-associated regulators of TCR signaling, such as the kinase Lck (lymphocyte-specific protein tyrosine kinase) and the adaptor LAT, also exploit recycling to move to the IS. 5,6 This mechanism has been suggested to ensure a long-lasting supply of receptors and signaling mediators at this location, which is essential to sustain signaling for the extended timeframe required for naive T-cell activation. The report by Larghi and collegues provides now evidence of a direct link between exocytic trafficking and TCR signaling at the IS by implicating the SNARE VAMP7 in the mobilization of vesicular subsynaptic LAT molecules close to TCR activation sites, where they become competent to orchestrate downstream signaling.…”
mentioning
confidence: 99%
“…8 In addition to being associated with the plasma membrane in the form of pre-existing clusters, LAT molecules also form an intracellular pool which partially colocalizes with transferrin positive recycling endosomes. 6 While both pools are recruited to the IS, with a rapid mobilization of plasma membraneassociated LAT and a more delayed mobilization for vesicular LAT, it is the intracellular pool of LAT that appears to be centrally required for full LATdependent TCR signaling. 6 This is further supported by recent findings showing that LAT molecules associated with subsynaptic vesicles, rather than LAT molecules forming pre-existing domains at the plasma membrane, are phosphorylated following TCR engagement.…”
mentioning
confidence: 99%
See 1 more Smart Citation